European open access policies in FP7: openAIRE’s infrastructure & support - Schmidt, Birgit (2011)
Access to scientific information is essential for a flourishing European Research Area. To put this into practice, the European Commission has started an open access pilot in the Seventh Framework Programme (FP7) in August 2008. This policy requires researchers funded in seven selected areas of the FP7 to deposit their publications in a repository and to make it available in open access. A similar requirement has been established by the European Research Council through their open access guidelines in 2007. OpenAIRE (Open Access Infrastructure for Research in Europe), a three-year project which started in December 2009, supports the Commission’s open access policy by developing an infrastructure for repository networks and a European helpdesk system to support researchers in depositing their research publications. All kinds of stakeholders are invited to join this process towards a wider sharing of knowledge: above all researchers and project coordinators, librarians and repository managers, policy makers as well as publishers and journal editors. Moreover, combining the EC/ECR’s open access policies with national and local open access initiatives can be a powerful match to bring open access forward in Europe. The poster describes what the open access policies expect from researchers, how institutions and repository managers can support them in complying with these requirements, and how this fits into OpenAIRE’s infrastructure and support network.